СОВРЕМЕННЫЕ МОДЕЛИ СОЦИАЛЬНЫХ ИССЛЕДОВАНИЙ В УСЛОВИЯХ РАЗВИТИЯ ЦИФРОВОЙ ИНФРАСТРУКТУРЫ - Z. T. Satpaeva (Экономика: стратегия и практика, 2018)
In order to study the information digital infrastructure of scientific research, an analysis of modern social research models was carried out. The study found that there are five models of digital infrastructure for social research. Each model is a minimal set of unifying concepts, axioms and relations in the field of social research. The choice of this or that model is determined by various factors. The findings of study results can be used to determine the priority directions for the development of the national model of social research digital infrastructure.